Studying the long-term causal relationship between Islamic sukuk and economic growth in Sudan for the period 2000-2019 - Samir Tamma; Yacine Hafsi Bouenbaou (Dirassat Journal Economic Issue, 2022)
The study aims to determine the causal sukuk Islamic instruments and economic growth in Sudan using the period 2000-2019 data, four variables (Islamic sukuk, final expenditures for general consumption of the government, Gross fixed capital formation) and per capita GDP as an indicator of of economic growth and to achieve the objectives of the study we used a range of approaches and economic measurement tools, from that test TODA and Yamamoto methodology for a long-term causal relationship as well as studying the motion of the autoregressive vector model VAR. Using the Eveiws 10 program. The study concluded that there is a unidirectional causal relationship that tends from the magnanimity of Islamic sukuk towards the per capita GDP in the long term, the study also found, through the movement of the pulse response functions of the VAR model, that occur in Islamic sukuk have a weak positive impact of different value according to periods on the per capita GDP, as it became clear that Islamic sukuk needs a long time to show its impact on growth economic.